2020
DOI: 10.2147/dddt.s218357
|View full text |Cite
|
Sign up to set email alerts
|

<p>Colon Targeting of Naringin for Enhanced Cytoprotection Against Indomethacin-Induced Colitis in Rabbits</p>

Abstract: Background: Naringin is a promising anti-inflammatory drug against various disorders including ulcerative colitis. However, its oral bioavailability is low (8%) possibly due to cleavage at the upper gut. Consequently, colon targeting would be necessary for drug protection at the upper gut, enhanced oral bioavailability and potentiated cytoprotection against colitis. Methodology: This study involved the formulation of compression-coated tablets of naringin employing mixtures of pH-sensitive Eudragit L100-55 (EU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 66 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Known food-grade delivery systems constructed from xanthan gum mixed with sodium alginate or xanthan gum with chitosan showed faster release profiles than our system [11,12]. Additionally, Naggar et al [15] revealed that a pharmaceutical coating employing methacrylic acid copolymer did not inhibit flowing out at all, and blend coatings with ethyl cellulose, sodium alginate, or sodium carboxymethyl cellulose strongly suppressed drug release in a pH 6.8 solution. These data indicate that our tablet system combined with the shellac coating and the use of HPMC inside possesses an advantage in controlled release compared to known food-grade technologies, though it does not achieve the level of control obtained using pharmaceutical additives.…”
Section: Formulation and Characterization Of Controlled-release Table...mentioning
confidence: 59%
See 1 more Smart Citation
“…Known food-grade delivery systems constructed from xanthan gum mixed with sodium alginate or xanthan gum with chitosan showed faster release profiles than our system [11,12]. Additionally, Naggar et al [15] revealed that a pharmaceutical coating employing methacrylic acid copolymer did not inhibit flowing out at all, and blend coatings with ethyl cellulose, sodium alginate, or sodium carboxymethyl cellulose strongly suppressed drug release in a pH 6.8 solution. These data indicate that our tablet system combined with the shellac coating and the use of HPMC inside possesses an advantage in controlled release compared to known food-grade technologies, though it does not achieve the level of control obtained using pharmaceutical additives.…”
Section: Formulation and Characterization Of Controlled-release Table...mentioning
confidence: 59%
“…However, it has not yet been reported whether the HPMC-containing tablets reached the lower-intestinal sites between the ileum and colon. As indicated by Naggar et al [15], not only HPMC but also a coating technology that protects the tablet from releasing its ingredients in the upper intestine upon exposure to gastric fluid would be necessary for effective gastrointestinal delivery. Shellac is permitted for use in food as a coating material.…”
Section: Introductionmentioning
confidence: 99%
“…-OH [33,37,38] 3439 3442 -OH bonds [40,45] 2919 -CH aliphatic group [37,38] 2929 2929 CH [44] 1644 Carbonyl group [39] 2883 CH [44] 1579 Benzene ring [39] 1738 1733 Carboxylic group [40] 1519 Benzene ring [39] 1628 1635 Carboxylic group [40,45] 1449 Benzene ring [39] 1519 Aromatic OH [63] 1367 -OH phenolic group [42,43] 1421 1416 COOÀ [41] 1296 -OH phenolic group [42,43] 1364 -OH phenolic group [42,43] 1264 Carboxylic group 1266 1267 Carboxylic group [40,45] 1202 -OH phenolic group [42,43] 1073 1074 Alginate ring [41] 1177 -OH phenolic group [42,43] 1030 1030 Alginate ring [41] 1132 -C-O-C [39] 822 822 CH group [41] 1090 Carbonyl group [39] 811 811 CH group [41] 1042 -C-O group [38] 671 671 CH group [41] 900-500 Bending vibration of the ring [43] 556 559 C-O [43] 500-400 500-400 C-C-C [43] immersion in PBS. The spheres release out naringin very fast after soaking.…”
mentioning
confidence: 99%